(3eSGdc GdCagGe Edi JfbjM TQGFY GdESdGes - (3LhGO Hf SYO Hf LOGO GdHZOGOj GdcGXei hjYQa HGdaGVd GdLhGO , J (B1065 (3g`s ((3eMeO Hf GdHQOhjdi GdYGedi s)
(3ChdgG (B:s
(3bhdg hgh SGjZ ai TQM GdESdGe dJMbb TQYg hYOe eG jOd Ydi QaYg s
(3BNQgG (B:s
(3GOi Edi GdNQGH h CTgQgeG GdYOe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3abg GdePGgH GdCNQis